2015
DOI: 10.1177/0271678x15606713
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen extraction fraction measurement using quantitative susceptibility mapping: Comparison with positron emission tomography

Abstract: The purposes of this study are to establish oxygen extraction fraction (OEF) measurements using quantitative susceptibility mapping (QSM) of magnetic resonance imaging (MRI), and to compare QSM-OEF data with the gold standard (15)O positron emission tomography (PET). Twenty-six patients with chronic unilateral internal carotid artery or middle cerebral artery stenosis or occlusion, and 15 normal subjects were included. MRI scans were conducted using a 3.0 Tesla scanner with a three-dimensional spoiled gradient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
134
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 91 publications
(139 citation statements)
references
References 28 publications
5
134
0
Order By: Relevance
“…Against our expectations, however, a recent study has demonstrated that QSM-OEF at 7T MR imaging achieved only a slight improvement in the correlation coefficient, and the sensitivity/specificity of OEF obtained with 15 O-PET included substantial systematic biases in terms of the agreements compared with that at 3T MR imaging. 22,23 This issue can be mainly attributed to the relatively low spatial resolution of the source images at 7T MR imaging, which was comparable with that at 3T MR imaging. 22,23 Although the blood oxygen level-dependent effect is much stronger at 7T MR imaging than at 3T MR imaging, susceptibility information of minute venous structures at 7T MR imaging was presumably overlooked due to the low resolution of the images.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Against our expectations, however, a recent study has demonstrated that QSM-OEF at 7T MR imaging achieved only a slight improvement in the correlation coefficient, and the sensitivity/specificity of OEF obtained with 15 O-PET included substantial systematic biases in terms of the agreements compared with that at 3T MR imaging. 22,23 This issue can be mainly attributed to the relatively low spatial resolution of the source images at 7T MR imaging, which was comparable with that at 3T MR imaging. 22,23 Although the blood oxygen level-dependent effect is much stronger at 7T MR imaging than at 3T MR imaging, susceptibility information of minute venous structures at 7T MR imaging was presumably overlooked due to the low resolution of the images.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 This issue can be mainly attributed to the relatively low spatial resolution of the source images at 7T MR imaging, which was comparable with that at 3T MR imaging. 22,23 Although the blood oxygen level-dependent effect is much stronger at 7T MR imaging than at 3T MR imaging, susceptibility information of minute venous structures at 7T MR imaging was presumably overlooked due to the low resolution of the images. 23 Thus, whereas the use of a 7T scanner in the present study is a significant limitation on the availability of QSM-OEF, the same results as in the present study could probably be obtained with QSM-OEF at 3T MR.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[93, 94] Early quantitative studies to measure oxygen saturation typically modeled large draining veins[95] and cortical vessels[96] as long cylinders parallel to the main field. With this assumed geometry and orientation, a simple relation exists between the measured field shift ΔB vein-water and the oxygen extraction fraction (OEF): ΔB vein-water = 4π Δχ do0 Hct OEF, where Δχ do0 is the susceptibility shift between fully oxygenated and fully deoxygenated blood.…”
Section: Future Directionsmentioning
confidence: 99%